“Cherenkov radiation” of a sound in a Bose condensed gas - Kovrizhin, D; Maksimov, L (Elsevier, 2001)
In terms of linearized Gross–Pitaevskii equation we have studied the process of sound emission arises from a supersonic particle motion in a Bose condensed gas. By analogy with the method used for description of Vavilov–Cherenkov phenomenon, we have found a friction work created by the particle generated condensate polarization. For comparison we have found radiation intensity of excitations. Both methods gives the same result.